Mechanics of materials - Riley, William F. (William Franklin) 1925- (John Wiley & Sons, 1999)
The text stresses the use of fundamental principles and the concepts of mechanics to solve all problems. As a result, students must apply the information presented in each chapter to answer realistic problems instead of simply using formulas. This problem solving method motivates students to learn the material because they see how it is used in the real world.